2508. Absolute Lymphocyte Count and Adenovirus-Specific CD8+ T-cell Immunity as Immunological Predictors of Severe Adenovirus Disease After Kidney Transplantation. (26th November 2018) - Bruminhent, Jackrapong; Apiwattanakul, Nopporn; Pinsai, Subencha; Thongprayoon, Charat; Hongeng, Suradej; Kantachuvessiri, Surasak; Watcharananan, Siriorn P
Abstract: Background: Adenovirus (ADV) infection after kidney transplantation (KT) can range from asymptomatic to severe disease. Cell-mediated immunity plays an important role in preventing disease progression. We aimed to investigate the role of absolute lymphocyte count (ALC) and ADV-specific CD8+ T cell immunity to predict the severity of ADV infection in KT recipients Methods: We included all adult KT recipients with ADV infection at a single transplant center between January 2015 and March 2018. ADV infection/disease were defined as detectable ADV DNA load in plasma/plus symptoms. We defined severe ADV disease as having plasma ADV DNA load >6.0 log copies/mL and/or disseminated disease (≥2 specific organ symptoms). ADV specific CD8+ T cells were stimulated with whole ADV peptide, stained by intracellular cytokine staining and interrogated by flow cytometry. ALC (all patients) and ADV-specific CD8+ T-cell (7 index cases) were measured at diagnosis. The association of ALC and disease progression were assessed in those with and without severe disease. Results: ADV infection was diagnosed in 14 KT recipients, 12 (86%) patients were male with a median age of 44 (IQR, 37–58) years. Ten (71%) recipients underwent deceased donor KT and none received anti-thymocyte globulin for induction therapy. ADV infection occurred at median of 14 (IQR, 2–37) months after KT. Eight (57%) recipients were defined as having severe ADV disease including disseminated ADV disease ( n = 5). Median peak plasma ADV load was higher in those with severe disease compared with those without severe disease [6.0 (IQR 5.9–6.0) vs. 5.3 (IQR 3.9–5.4) log copies/mL ( P = 0.003)]. Median ALC and ADV-specific CD8+ T cells at diagnosis were 1, 000 (IQR 623–1, 350) and 0.003 cells/mm 3, respectively. KT recipients with severe disease had lower median ALC at diagnosis compared with those without severe disease [714 (IQR 419–860) vs. 1, 264 (IQR 972–2, 086) cells/mm 3 ; P = 0.04) (Figure 1). Those with ALC <1, 000 cells/mm 3 at diagnosis had greater risk of severe disease [OR 35 (95% CI, 2.6–1, 450); P = 0.006]. Conclusion: Lack of ALC and ADV-specific CD8+ T cell immunity (limited data) at diagnosis could potentially be immunological predictors of severe ADV infection in KT recipients. Disclosures: All authors: No reported disclosures.